Anti-fogging resin sheet and its secondary molded product
The antifog resin sheet, featuring an antifog layer with sucrose fatty acid ester and cyclodextrin, and a silicone oil release layer, addresses the challenges of fogging, agent displacement, and dust adhesion by achieving superior antifog, anti-back displacement, and anti-static properties.
Patent Information
- Application Number
- JP2021036305
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-08
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2041-03-08
AI Technical Summary
Existing antifog resin sheets fail to simultaneously achieve excellent antifog, anti-back displacement, and anti-static properties, leading to issues such as fogging, agent displacement, and dust adhesion.
An antifog resin sheet with an antifog layer composed of sucrose fatty acid ester, polyvinylpyrrolidone, cyclodextrin or its derivative, and sulfate ester salt, along with a release layer of silicone oil on the opposite surface, is developed to enhance antifog, anti-back displacement, and anti-static properties.
The proposed antifog resin sheet effectively maintains excellent antifog, anti-back displacement, and anti-static properties, preventing fogging, agent displacement, and dust adhesion, thus meeting all required performance criteria.
Smart Images

Figure 0007658757000001 
Figure 0007658757000002
Abstract
Description
[Technical field]
[0001] The present invention relates to an anti-fogging resin sheet for use in food packaging containers and various other containers, and to a secondary molded product thereof. [Background technology]
[0002] Resin sheets extruded from various thermoplastic resins are heated and molded into secondary forms using a vacuum forming machine, a compressed air vacuum forming machine, a hot plate compressed air forming machine, etc., and the secondary molded products obtained are widely used for packaging lightweight food packaging containers and other items. Among these resin sheets, transparent resin sheets such as polystyrene, polyethylene terephthalate, polypropylene, etc. are widely used as lid materials for lunch boxes, side dish containers, etc., due to their transparency. However, these lid materials have a problem in that the inner surface of the lid material becomes cloudy due to water vapor generated from the contents.
[0003] Furthermore, when this transparent resin sheet is subjected to secondary molding to manufacture a secondary molded product such as a lid material, a process is performed in which a large number of secondary molded resin sheets are stacked and punched out together. During this punching process, the secondary molded products tend to adhere to each other, which causes the problem that it is difficult to peel off and remove each of the stacked secondary molded products one by one.
[0004] As a method for solving the above problems, for example, a method has been proposed in which an aqueous solution containing a sucrose fatty acid ester, polyvinyl alcohol and a silicone emulsion as an anti-fogging agent is applied to one side of a resin sheet (see, for example, Patent Document 1).
[0005] Also, for example, a method has been proposed in which a surface treatment agent containing a sucrose fatty acid ester, a polysaccharide, and a silicone emulsion as an anti-fogging agent is applied to one side of a resin sheet (see, for example, Patent Document 2).
[0006] As a means for improving anti-fogging properties, a sheet has been proposed which has an anti-fogging layer containing a sucrose fatty acid ester (A), cyclodextrin and / or its derivative (B), and polyvinyl alcohol (C) to provide a sheet with excellent appearance and excellent high-temperature and low-temperature anti-fogging properties regardless of the molding method and mold shape (see, for example, Patent Document 3).
[0007] Furthermore, a sheet has been proposed that combines a nonionic surfactant (such as a sucrose fatty acid ester), a water-soluble polymer (such as a vinylpyrrolidone-based polymer), and an anionic surfactant (such as a sulfonate salt) to obtain high anti-fogging properties over a wide range of temperatures, and that does not contaminate rolls (particularly metal rolls) and does not cause offset in the resin sheet manufacturing process (see, for example, Patent Document 4). [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Japanese Patent Application Publication No. 56-166234 [Patent Document 2] Japanese Patent Application Publication No. 5-287097 [Patent Document 3] JP 2007-185951 A [Patent Document 4] JP 2010-37387 A Summary of the Invention [Problem to be solved by the invention]
[0009] By the way, anti-fogging resin sheets coated with an anti-fogging agent are usually wound into a roll and supplied to the market as wound products. If the anti-fogging agent is transferred to the back side when wound into a wound product, the appearance and anti-fogging properties of the sheet are deteriorated, so it is necessary to prevent the anti-fogging agent from transferring to the back side when wound into a wound product. In particular, in recent years, even when wound products are supplied under harsh environments, it is necessary to stably supply good wound products, and the demand for preventing the anti-fogging agent from transferring to the back side in wound products is increasing. Under such circumstances, the present inventors evaluated the offset of the anti-fog resin sheet described in the above Patent Document 4. In this evaluation, the offset was evaluated under more severe conditions in consideration of the level of practical application, rather than using the evaluation criteria for offset described in the above Patent Document 4. As a result, as shown in the comparative example below, it was found that in an anti-fog resin sheet made of sucrose fatty acid ester, polyvinylpyrrolidone, and sodium lauryl ether sulfate as described in the above Patent Document 4, the sheets tend to adhere to each other, blocking occurs, and offset of the anti-fog agent occurs, and offset of the anti-fog agent cannot be effectively prevented when the sheet is rolled up. Further, anti-fog resin sheets are required to have not only high anti-fog properties and anti-offset properties, but also anti-static properties to prevent dust and foreign matter from adhering to the sheet or secondary molded product. However, it has been found that the anti-fog resin sheet described in Patent Document 3 above has insufficient antistatic properties on the surface coated with the anti-fog agent, and dust and foreign matter are likely to adhere to the sheet and secondary molded products.
[0010] So far, no anti-fog resin sheet has been provided that can satisfy all of good anti-fog properties, good anti-offset properties, and good antistatic properties.
[0011] Therefore, an object of the present invention is to provide an anti-fog resin sheet that can satisfy all of good anti-fog properties, good anti-offset properties, and good antistatic properties. [Means for solving the problem]
[0012] As a result of intensive research into solving the above-mentioned problems, the present inventors have found that when an anti-fog resin sheet is formed using an anti-fog layer made of an anti-fog agent containing a sucrose fatty acid ester (A), polyvinylpyrrolidone (B), cyclodextrin and / or a derivative thereof (C), and a sulfate salt (D), an anti-fog resin sheet that can satisfy all of good anti-fog properties, good anti-offset properties, and good antistatic properties can be obtained, thereby completing the present invention.
[0013] That is, the present invention includes the following aspects. [1] An anti-fog resin sheet comprising a thermoplastic resin sheet and an anti-fog layer formed on at least one surface thereof, the anti-fog layer comprising an anti-fog agent containing a sucrose fatty acid ester (A), polyvinylpyrrolidone (B), cyclodextrin and / or a derivative thereof (C), and a sulfate ester salt (D). [2] The anti-fog resin sheet according to [1], wherein the cyclodextrin is a single member selected from the group consisting of α-cyclodextrin, β-cyclodextrin and γ-cyclodextrin, or a mixture of two or more members selected from the group consisting of α-cyclodextrin, β-cyclodextrin and γ-cyclodextrin. [3] The anti-fog resin sheet according to [1] or [2], wherein a release layer made of silicone oil (E) is formed on the other side of the thermoplastic resin sheet opposite to the side on which the anti-fog layer is provided. [4] The anti-fog resin sheet according to any one of [1] to [3], wherein the thermoplastic resin sheet is a styrene-based resin sheet. [5] A secondary molded product obtained by molding the anti-fog resin sheet according to any one of [1] to [4]. Effect of the Invention
[0014] According to the present invention, it is possible to provide an anti-fog resin sheet that can satisfy all of good anti-fog properties, good anti-offset properties, and good antistatic properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The present invention will be described in detail below. Note that the following description of the constituent elements is merely an example for explaining the present invention, and the present invention is not limited to the contents thereof.
[0016] (Anti-fogging resin sheet) The anti-fog resin sheet of the present invention has a thermoplastic resin sheet and an anti-fog layer. The anti-fogging layer is formed on at least one surface of the thermoplastic resin sheet. The anti-fogging layer is formed using an anti-fogging agent. The anti-fogging resin sheet of the present invention may further have a release layer. The release layer is preferably formed on the other surface of the thermoplastic resin sheet opposite to the surface on which the anti-fogging layer is provided.
[0017] <Thermoplastic resin sheet> The type of resin for the thermoplastic resin sheet serving as the substrate of the anti-fog resin sheet of the present invention is not particularly limited, but is preferably transparent, and examples thereof include styrene-based resins such as polystyrene, crystalline polystyrene, styrene-butadiene copolymer, styrene-isoprene-styrene copolymer, styrene-isoprene-butadiene-styrene copolymer, styrene-ethylene-butadiene-styrene copolymer, transparent styrene-butadiene-(meth)acrylic acid alkyl ester copolymer, styrene-(meth)acrylic acid copolymer, styrene-maleic anhydride copolymer, and styrene-(meth)acrylic acid alkyl ester copolymer; propylene-based resins such as polypropylene, propylene-butadiene copolymer, and ethylene-propylene copolymer; polycarbonate, polyvinyl chloride, polyvinylidene chloride, polyamide resins such as nylon 6, and polyester resins such as polyethylene terephthalate are preferred.
[0018] In addition, two or more of these resins may be mixed and used as long as the transparency of the anti-fog resin sheet of the present invention is not impaired. Furthermore, these thermoplastic resin sheets may be multi-layered sheets of two or more layers using one or more of these resins. Furthermore, these thermoplastic resin sheets may be subjected to uniaxial or biaxial stretching treatment.
[0019] Furthermore, biaxially oriented polystyrene resin sheets are often heated and molded using a hot plate compressed air molding machine, and in this case, when a conventional antifogging agent is used, the antifogging property of the molded body during heating and molding tends to decrease significantly. However, in the antifogging resin sheet of the present invention, even when a biaxially oriented polystyrene resin sheet is used as the substrate, a secondary molded product having excellent antifogging property can be obtained. From the viewpoint of compatibility with a general-purpose hot plate compressed air molding machine, a polystyrene resin sheet is preferred as the substrate for the antifogging resin sheet of the present invention, and a biaxially oriented polystyrene resin sheet is most preferred.
[0020] The thickness of these thermoplastic resin sheets is not particularly limited, but is preferably 0.05 to 1.0 mm from the viewpoint of the rigidity and strength of the secondary molded product when the anti-fogging resin sheet is secondary molded.
[0021] In the resins used for these thermoplastic resin sheets, various fine particles for producing protrusions on the surface of the resin sheet can be added to prevent blocking of the anti-fog resin sheet, within a range that does not impair the transparency of the resin sheet. Examples of the fine particles include resin crosslinked beads such as styrene-based resin crosslinked beads, (meth)acrylic acid ester-based resin crosslinked beads, and polyurethane-based resin crosslinked beads, inorganic fine particles such as silica, hydrophobized silica, spherical silica, soft calcium carbonate, titanium oxide, and talc, and rubber fine particles. For rubber fine particles, a method of using a rubber-containing resin in combination is exemplified. The rubber-containing resin used here is different from the thermoplastic resin that is the base material of the anti-fogging resin sheet, and examples of the rubber-containing resin include high impact polystyrene (HIPS), styrene-acrylonitrile-butadiene copolymer (ABS), styrene-ethylene-butadiene-styrene copolymer (SEBS), styrene-butadiene-(meth)acrylic acid ester copolymer (MBS), and high impact (meth)acrylic acid ester (HI-PMMA).
[0022] <Anti-fogging layer> The anti-fogging layer is formed using an anti-fogging agent. The anti-fogging agent contains a sucrose fatty acid ester (A), polyvinylpyrrolidone (B), cyclodextrin and / or a derivative thereof (C), and a sulfate salt (D).
[0023] <<Sucrose fatty acid ester (A)>> Examples of the sucrose fatty acid ester (A) include those obtained by transesterification of sucrose with a lower alcohol ester of a fatty acid, such as a fatty acid methyl ester. Specific examples include sucrose stearate, sucrose palmitate, sucrose laurate, and sucrose oleate. These sucrose fatty acid esters can be used alone or in combination of two or more kinds. Sucrose fatty acid esters include monoesters, diesters and triesters, and in order to obtain better sheet appearance and anti-fogging effect, it is preferable that the sucrose fatty acid monoester content is 50 mol% or more and that the HLB value (hydrophilic-lipophilic balance) is 13 to 17. That is, by making the HLB value 13 or more, it becomes possible to coat the sheet uniformly due to high water solubility, and a better sheet appearance can be obtained, and by making the HLB value less than 17, better anti-fogging properties can be obtained.
[0024] <<Polyvinylpyrrolidone (B)>> The weight average molecular weight (Mw) of polyvinylpyrrolidone (B) is not particularly limited, but is, for example, preferably in the range of 8,000 to 3,000,000, more preferably in the range of 20,000 to 2,000,000, and further preferably in the range of 40,000 to 1,500,000.Within the range of 8,000 to 3,000,000, the smaller the weight average molecular weight of polyvinylpyrrolidone is, the higher the anti-fogging properties can be obtained, and the larger the weight average molecular weight is, the higher the heat resistance (resistance to yellowing caused by heat) can be obtained.
[0025] The polyvinylpyrrolidone may be a commercially available product, and the commercially available product of polyvinylpyrrolidone may be in the form of a powder or a solution. In addition, for example, two or more kinds of polyvinylpyrrolidone having different weight average molecular weights may be used in combination.
[0026] Polyvinylpyrrolidone is typically a polymer composed of vinylpyrrolidone alone, but may be a copolymer of vinylpyrrolidone and other monomers as long as the effect of the present invention is not impaired. Examples of other monomers include acrylic acid esters, acrylic acid, methacrylic acid esters, methacrylic acid, styrene, vinyl acetate, etc. Polyvinylpyrrolidone may also be a block polymer or a graft polymer composed of a vinylpyrrolidone block and a polyvinyl alcohol block of another monomer.
[0027] <<Cyclodextrin and / or its derivatives (C)>> Examples of cyclodextrin include α-cyclodextrin in which 6 D-glucose units are bonded, β-cyclodextrin in which 7 D-glucose units are bonded, and γ-cyclodextrin in which 8 D-glucose units are bonded.
[0028] From the viewpoints of water solubility and antifogging properties, the cyclodextrin used in the present invention is preferably selected from the group consisting of α-cyclodextrin, β-cyclodextrin and γ-cyclodextrin. Although the cyclodextrin may be a single substance, it is more preferable that the cyclodextrin be a mixture of two or three types selected from this group of cyclodextrins.
[0029] Examples of cyclodextrin derivatives include alkylated cyclodextrins such as dimethyl cyclodextrin, trimethyl cyclodextrin, diethyl cyclodextrin, triethyl cyclodextrin, tripropyl cyclodextrin, and tributyl cyclodextrin; acylated cyclodextrins such as triacetyl cyclodextrin, tripropionyl cyclodextrin, and tributanoyl cyclodextrin; hydroxyalkylated cyclodextrins such as hydroxypropyl cyclodextrin; and maltosyl cyclodextrin in which maltose has been introduced as a branched chain.
[0030] <<Sulfate ester salts (D)>> Examples of sulfate salts include alkyl sulfate salts (such as sodium lauryl sulfate), alkenyl sulfate salts such as oleyl sulfate salts (such as sodium oleyl sulfate), and alkyl ether sulfate salts (sodium lauryl ether sulfate, polyoxyethylene alkyl ether sulfate, etc.).
[0031] The content of the sucrose fatty acid ester (A) according to the present invention is preferably 0.5 to 5.0 parts by mass, and more preferably 0.5 to 3.0 parts by mass, relative to 100 parts by mass of the aqueous solution containing the antifogging agent of the present invention. The content of polyvinylpyrrolidone (B) according to the present invention is preferably 0.1 to 2.0 parts by mass, and more preferably 0.2 to 1.0 part by mass, relative to 100 parts by mass of the aqueous solution containing the antifogging agent of the present invention. The content of the cyclodextrin and / or derivative thereof (C) according to the present invention is preferably 0.1 to 1.0 part by mass, more preferably 0.15 to 0.8 part by mass, and even more preferably 0.2 to 0.6 part by mass, relative to 100 parts by mass of the aqueous solution containing the antifogging agent of the present invention. The content of the sulfate salt (D) according to the present invention is preferably 0.05 to 1.0 part by mass, and more preferably 0.1 to 0.8 part by mass, relative to 100 parts by mass of the aqueous solution containing the antifogging agent of the present invention.
[0032] The content of polyvinylpyrrolidone (B) in the antifogging agent according to the present invention is preferably 10.4 to 208 parts by mass, and more preferably 20.8 to 104 parts by mass, per 100 parts by mass of the sucrose fatty acid ester (A). The content of cyclodextrin and / or its derivative (C) in the antifogging agent according to the present invention is preferably 10.4 to 104 parts by mass, more preferably 15.7 to 83.3 parts by mass, and even more preferably 20.8 to 62.5 parts by mass, per 100 parts by mass of the sucrose fatty acid ester (A). The content of the sulfate salt (D) in the antifogging agent according to the present invention is preferably 5.20 to 104 parts by mass, and more preferably 10.4 to 83.3 parts by mass, per 100 parts by mass of the sucrose fatty acid ester (A).
[0033] The antifogging agent forming the antifogging layer of the present invention may contain a nonionic surfactant other than the sucrose fatty acid ester (A) within a range that does not impair the effects of the present invention.
[0034] <Release layer> In the present invention, a release layer can be formed by applying a release agent to the surface of the thermoplastic resin sheet opposite to the surface on which the anti-fogging layer is provided. As the release agent, silicone oil (E) can be used. From the viewpoints of safety and economy, this silicone oil (E) has a viscosity of 1,000,000 to 500,000 mm at 25°C. 2 Dimethylpolysiloxanes in the range of 1 / s are preferred.
[0035] In addition, when applying the silicone oil (E) to the surface of the thermoplastic resin sheet, it is preferable to use it in the form of a silicone emulsion. The average particle size of the silicone oil (E) in the silicone emulsion is preferably 1 μm or less. That is, if the average particle size exceeds 1 μm, it is difficult to apply the silicone oil uniformly, and the appearance of the anti-fog resin sheet is deteriorated.
[0036] In addition, the silicone oil (E) used in the present invention is preferably applied to the other side of the surface coated with the antifogging agent, since the appearance of the sheet or secondary molded product is improved. That is, when the silicone oil (E) is mixed and applied in the antifogging agent, there is a problem that the appearance of the sheet or secondary molded product is deteriorated, so the amount of silicone oil (E) needs to be 10.0 parts by mass or less for 100 parts by mass of the aqueous solution containing the antifogging agent of the present invention. Furthermore, it is preferable to make it 5.0 parts by mass or less, and it is particularly preferable that the antifogging agent does not contain silicone oil.
[0037] Furthermore, it is also possible to add a surfactant having an antistatic effect, a lubricant, etc. to the silicone emulsion liquid containing the silicone oil (E) used in the present invention.
[0038] <Method for manufacturing anti-fogging resin sheet> The method for producing the anti-fogging resin sheet of the present invention involves, for example, applying an anti-fogging agent in a solution form containing a sucrose fatty acid ester (A), polyvinylpyrrolidone (B), cyclodextrin and / or a derivative thereof (C), and a sulfate ester salt (D) to at least one surface of a thermoplastic resin sheet, and then drying the solvent to form an anti-fogging layer.
[0039] The method for producing the anti-fog resin sheet of the present invention is not particularly limited, but it is preferable to apply an anti-fog agent consisting of an aqueous solution to at least one surface of a thermoplastic resin sheet obtained by forming a film from a thermoplastic resin by a known method. Specifically, there can be mentioned a method in which one surface of a thermoplastic resin sheet is subjected to a hydrophilization treatment, and then the anti-fog agent of the present invention is applied to this treated surface, and the solvent is dried to form an anti-fog layer.
[0040] The method for applying the anti-fog agent used in the manufacturing method of the anti-fog resin sheet of the present invention includes known methods such as a spray coater, roll coater, gravure roll coater, knife coater, air knife coater, rotor dampening coater, and applicator system, and is not particularly limited.
[0041] The coating amount of the antifogging agent in the antifogging resin sheet of the present invention is preferably adjusted to a predetermined amount in order to improve the antifogging effect and prevent poor appearance due to uneven coating. Specifically, the coating amount of the solid content after drying, that is, the mass of the antifogging layer per unit area of the antifogging resin sheet, is 5 to 1,000 mg / m. 2 is preferably 5 to 150 mg / m 2 It is particularly preferred that:
[0042] Quantitative analysis of the amount of anti-fog agent applied can be performed by Fourier transform infrared spectrophotometer analysis (multiple internal reflection method) [FTIR analysis (ATR method)].
[0043] In addition, examples of the method for hydrophilizing the surface of the thermoplastic resin sheet include known methods such as acid treatment, flame treatment, and corona treatment. The surface of the thermoplastic resin sheet subjected to such hydrophilization treatment preferably has a wet tension of 38 mN / m or more, and more preferably has a wet tension of 45 to 60 mN / m in order to uniformly apply the antifogging agent and obtain a sufficient antifogging effect. Here, the wet tension is a value measured by the method described in JIS K6768-1999.
[0044] (Secondary molded product) By molding the anti-fogging resin sheet of the present invention by means of vacuum forming, compressed air vacuum forming, hot plate compressed air forming, or the like, it is possible to produce secondary molded products suitable for food containers such as lunch containers, side dish containers, sushi containers, and sashimi containers, particularly anti-fogging transparent lids for such food containers. EXAMPLES
[0045] The present invention will be described in more detail below with reference to examples, but the scope of the present invention is not limited to these examples.
[0046] Example 1 An anti-fogging agent (1) was obtained by mixing and dissolving 0.96 mass% of sucrose laurate (monoester 72 mol%, HLB 15), 0.20 mass% of cyclodextrin (cyclodextrin purity 97% or more, of which α-cyclodextrin 70% or more), 0.43 mass% of polyvinylpyrrolidone (K value 94, weight average molecular weight 1,200,000), and 0.17 mass% of sodium polyoxyethylene lauryl ether sulfate in 98.24 mass% of water.
[0047] Next, one side of a 0.21 mm thick biaxially oriented polystyrene resin sheet (Sandic Sheet 510, manufactured by Sandic Co., Ltd.) that had not been subjected to any coating treatment on its surface was subjected to a corona treatment with a wetting tension of 50 mN / m, and an anti-fog agent was applied to the corona-treated surface in a solid content of 50 mg / m using a roll coater method. 2 The antifogging agent (1) was appropriately diluted with water so as to obtain the above-mentioned antifogging layer, which was then dried with a dryer to obtain an antifogging layer.
[0048] Furthermore, a 2.5% by mass aqueous solution of silicone emulsion ("SM7025EX" manufactured by Dow Toray Industries, Inc., silicone oil content 33% by mass) was applied to the surface of the sheet opposite to the surface on which the anti-fog layer was provided, using a roll coater, dried with a dryer, and then wound up into a roll to obtain an anti-fog resin sheet (1).
[0049] The amounts of anti-fog agent and silicone oil applied were determined by measuring the infrared absorption spectrum of the sheet surface using a Fourier transform infrared spectrophotometer (FTIR) with the multiple internal reflection method (ATR method), and performing quantitative analysis based on a calibration curve created from standard samples with known application amounts.
[0050] The obtained anti-fogging resin sheet (1) was molded using a hot plate compressed air molding machine with a hot plate temperature of 125° C. and a mold shown below to obtain a secondary molded product (1). Mold: 94mm (length) x 94mm (width) x 30mm (depth), corners: 2R
[0051] Example 2 An anti-fogging agent (2) was obtained by mixing and dissolving 0.96 mass% of sucrose laurate (monoester 72 mol%, HLB 15), 0.30 mass% of cyclodextrin (cyclodextrin purity 97% or more, of which α-cyclodextrin 70% or more), 0.43 mass% of polyvinylpyrrolidone (K value 94, weight average molecular weight 1,200,000), and 0.17 mass% of sodium polyoxyethylene lauryl ether sulfate in 98.14 mass% of water. Next, an anti-fogging resin sheet (2) and a secondary molded product (2) were obtained in the same manner as in Example 1, except that the obtained anti-fogging agent (2) was used.
[0052] Example 3 An anti-fogging agent (3) was obtained by mixing and dissolving 0.96 mass% of sucrose laurate (monoester 72 mol%, HLB 15), 0.60 mass% of cyclodextrin (cyclodextrin purity 97% or more, of which α-cyclodextrin 70% or more), 0.43 mass% of polyvinylpyrrolidone (K value 94, weight average molecular weight 1,200,000), and 0.17 mass% of sodium polyoxyethylene lauryl ether sulfate in 97.84 mass% of water. Next, an anti-fogging resin sheet (3) and a secondary molded product (3) were obtained in the same manner as in Example 1, except that the obtained anti-fogging agent (3) was used.
[0053] Example 4 An anti-fogging agent (4) was obtained by mixing and dissolving 0.96 mass% of sucrose laurate (monoester 72 mol%, HLB 15), 0.11 mass% of cyclodextrin (cyclodextrin purity 97% or more, of which α-cyclodextrin 70% or more), 0.43 mass% of polyvinylpyrrolidone (K value 94, weight average molecular weight 1,200,000), and 0.17 mass% of sodium polyoxyethylene lauryl ether sulfate in 98.33 mass% of water. Next, an anti-fogging resin sheet (4) and a secondary molded product (4) were obtained in the same manner as in Example 1, except that the obtained anti-fogging agent (4) was used.
[0054] Example 5 An anti-fogging agent (5) was obtained by mixing and dissolving 0.96 mass% of sucrose laurate (monoester 72 mol%, HLB 15), 0.90 mass% of cyclodextrin (cyclodextrin purity 97% or more, of which α-cyclodextrin 70% or more), 0.43 mass% of polyvinylpyrrolidone (K value 94, weight average molecular weight 1,200,000), and 0.17 mass% of sodium polyoxyethylene lauryl ether sulfate in 97.54 mass% of water. Next, an anti-fogging resin sheet (5) and a secondary molded product (5) were obtained in the same manner as in Example 1, except that the obtained anti-fogging agent (5) was used.
[0055] Comparative Example 1 0.96 mass% of sucrose laurate (monoester 72 mol%, HLB 15) and 0.20 mass% of cyclodextrin (cyclodextrin purity 97% or more, of which α-cyclodextrin 70% or more) were mixed and dissolved in 98.84 mass% of water to obtain an anti-fogging agent (6). Next, an anti-fogging resin sheet (6) and a secondary molded product (6) were obtained in the same manner as in Example 1, except that the obtained anti-fogging agent (6) was used.
[0056] Comparative Example 2 0.96 mass% of sucrose laurate (monoester 72 mol%, HLB 15), 0.43 mass% of polyvinylpyrrolidone (K value 94, weight average molecular weight 1,200,000), and 0.17 mass% of sodium polyoxyethylene lauryl ether sulfate were mixed and dissolved in 98.44 mass% of water to obtain an anti-fogging agent (7). Next, an anti-fogging resin sheet (7) and a secondary molded product (7) were obtained in the same manner as in Example 1, except that the obtained anti-fogging agent (7) was used.
[0057] Comparative Example 3 An anti-fogging agent (8) was obtained by mixing and dissolving 0.90 mass% of cyclodextrin (cyclodextrin purity of 97% or more, of which α-cyclodextrin is 70% or more) and 0.43 mass% of polyvinylpyrrolidone (K value 94, weight average molecular weight 1,200,000) in 98.67 mass% of water. Next, an anti-fogging resin sheet (8) and a secondary molded product (8) were obtained in the same manner as in Example 1, except that the obtained anti-fogging agent (8) was used.
[0058] Comparative Example 4 An anti-fogging agent (9) was obtained by mixing and dissolving 0.90 mass % of cyclodextrin (having a cyclodextrin purity of 97% or more, of which α-cyclodextrin is 70% or more) and 0.17 mass % of sodium polyoxyethylene lauryl ether sulfate in 98.93 mass % of water. Next, an anti-fogging resin sheet (9) and a secondary molded product (9) were obtained in the same manner as in Example 1, except that the obtained anti-fogging agent (9) was used.
[0059] Comparative Example 5 An anti-fogging agent (10) was obtained by mixing and dissolving 0.96 mass% of sucrose laurate (monoester 72 mol%, HLB 15), 0.20 mass% of cyclodextrin (cyclodextrin purity 97% or more, of which α-cyclodextrin 70% or more) and 0.43 mass% of polyvinylpyrrolidone (K value 94, weight average molecular weight 1,200,000) in 98.41 mass% of water. Next, an anti-fogging resin sheet (10) and a secondary molded product (10) were obtained in the same manner as in Example 1, except that the obtained anti-fogging agent (10) was used.
[0060] Comparative Example 6 An anti-fogging agent (11) was obtained by mixing and dissolving 0.96 mass% of sucrose laurate (monoester 72 mol%, HLB 15), 0.20 mass% of cyclodextrin (cyclodextrin purity 97% or more, of which α-cyclodextrin is 70% or more) and 0.17 mass% of sodium polyoxyethylene lauryl ether sulfate in 98.67 mass% of water. Next, an anti-fogging resin sheet (11) and a secondary molded product (11) were obtained in the same manner as in Example 1, except that the obtained anti-fogging agent (11) was used.
[0061] The anti-fog resin sheets (1) to (11) obtained above were evaluated for sheet appearance, antistatic property, anti-fog agent transfer property, and anti-fog property according to the following methods.
[0062] (Evaluation of Appearance of Anti-Fog Resin Sheet) The sheet after application of the antifogging agent was visually observed to evaluate the presence or absence of whitening of the sheet. The lower the degree of whitening of the sheet, the better the appearance of the antifogging resin sheet. [Evaluation Criteria] ○: The sheet after application does not turn white and maintains transparency. △: The sheet after application is slightly whitened, but at a level that does not interfere with practical use. ×: The sheet after application was whitened and the transparency was significantly reduced.
[0063] (Evaluation of antistatic properties of anti-fogging resin sheet) The surface resistance of the anti-fog agent-coated surface of the anti-fog resin sheet was measured using a microcurrent meter manufactured by Advantest Corp. The lower the surface resistance of the anti-fog agent-coated surface, the better the anti-fog resin sheet's antistatic properties. [Evaluation Criteria] ○:Surface resistance 1.0×10 13 Ω or less △:Surface resistance 1.0×10 13 Larger than 1.0×10 14 Ω or less ×: Surface resistance 1.0×10 14 Greater than Ω
[0064] (Evaluation of anti-fogging properties of secondary molded products) In order to evaluate the anti-fogging properties assuming the case where the contents are seen through from the outside when used in a high-temperature food container, the high-temperature anti-fogging properties of the secondary molded product were evaluated as follows. That is, a base material (obtained by secondary molding of a thermoplastic resin sheet) having the same shape as the secondary molded product was prepared, and a paper with a 15 mm square checkerboard pattern printed thereon was placed on it. After that, 100 mL of hot water at 90°C was poured into the base material, and the top of the base material was covered with the secondary molded product obtained in the above examples and comparative examples. The upper part of the base material was then covered with the secondary molded product obtained in the above examples and comparative examples. The upper part was then left at 23°C for 5 minutes, and the degree of distortion of the checkerboard pattern visible through the secondary molded product and the degree of water droplets attached to the top surface and the inside of the four corners were visually observed. The less the secondary molded product was clouded, or the less the checkerboard pattern was visually distorted, the better the anti-fogging properties of the anti-fogging resin sheet. [Evaluation Criteria] ○: The secondary molded product is not cloudy, and the checkerboard pattern is visible without distortion over 85% or more of the area of the secondary molded product. △: The secondary molded product is not cloudy, but the checkerboard pattern appears distorted over an area larger than 15% of the secondary molded product. ×: Small water droplets adhere to the top surface or four corners of the secondary molded product, making it cloudy.
[0065] (Evaluation of Anti-Fog Agent Anti-Offset Property) The anti-fog resin sheet was cut into 10cm x 10cm pieces, and the anti-fog agent-coated surface and the silicone-coated surface of the cut sheet were overlapped, and the sheet was heated and pressed at 50°C, 10MPa, and pressure for 30 minutes, and then cooled at room temperature for 2 hours. The overlapped sheets were then peeled off, and the presence or absence of transfer marks of the anti-fog agent was visually evaluated. The fewer the transfer marks of the anti-fog agent, the better the anti-fog resin sheet's anti-offset properties. [Evaluation Criteria] ○: Almost no traces of anti-fog agent transfer, and the sheet appearance is good △: There are slight traces of anti-fog agent transferred, but it is at a level that does not interfere with practical use. ×: Anti-fog agent transfer marks are generated, and the sheet has a poor appearance.
[0066] The evaluation results of Examples 1 to 5 and Comparative Examples 1 to 6 are shown in Tables 1 and 2.
[0067] [Table 1]
[0068] [Table 2]
[0069] The anti-fog resin sheet (1) of Example 1 had good sheet appearance, antistatic properties, and anti-fog properties, and there was almost no transfer of the anti-fog agent to the back side. The anti-fog resin sheets (2) and (3) of Examples 2 and 3 also had good sheet appearance, antistatic properties, anti-fog properties, and anti-offset properties. The anti-fog resin sheet (4) of Example 4 had good sheet appearance, antistatic properties, and anti-fog properties. Transfer marks of the anti-fog agent were generated, but this did not hinder practical use, and a transparent container could be obtained by secondary molding. The anti-fog resin sheet (5) of Example 5 was slightly whitened, but this did not hinder practical use, and a transparent container could be obtained by secondary molding. The antistatic property, anti-fog property, and anti-offset property were good. The anti-fog resin sheet (6) of Comparative Example 1 was good in sheet appearance and anti-offset properties, but was insufficient in anti-fog properties and anti-static properties. The anti-fog resin sheet (7) of Comparative Example 2 was good in sheet appearance, antistatic property and anti-fog property, but had poor anti-offset property of the anti-fog agent, and transfer marks of the anti-fog agent were generated. The anti-fog resin sheet (8) of Comparative Example 3 was good in sheet appearance and anti-offset properties, but was insufficient in anti-fog properties and anti-static properties. The anti-fog resin sheet (9) of Comparative Example 4 was good in the sheet appearance, antistatic property, and anti-offset property, but was insufficient in the anti-fog property. The anti-fog resin sheet (10) of Comparative Example 5 had an acceptable level of anti-offset property, but was slightly inferior in sheet appearance and anti-fog property, and had insufficient antistatic property. The anti-fog resin sheet (11) of Comparative Example 6 was good in the sheet appearance, antistatic property, and anti-offset property, but was insufficient in the anti-fog property.
[0070] The results shown in Table 1 demonstrate that the anti-fog resin sheets obtained in the examples exhibited satisfactory results in all respects, including good anti-fog properties, good anti-offset properties, and good antistatic properties.
Claims
1. An anti-fogging resin sheet comprising a thermoplastic resin sheet and an anti-fogging layer formed on at least one surface thereof, the anti-fogging layer comprising an anti-fogging agent containing a sucrose fatty acid ester (A), polyvinylpyrrolidone (B), cyclodextrin and / or a derivative thereof (C), and a sulfate ester salt (D), a content ratio of the sucrose fatty acid ester (A) relative to 100 parts by mass of the aqueous solution containing the antifogging agent is 0.5 parts by mass to 5.0 parts by mass, a content ratio of the polyvinylpyrrolidone (B) relative to 100 parts by mass of the aqueous solution containing the antifogging agent is 0.1 parts by mass to 2.0 parts by mass, a content ratio of the cyclodextrin and / or a derivative thereof (C) relative to 100 parts by mass of the aqueous solution containing the antifogging agent is 0.1 parts by mass to 1.0 parts by mass; The content ratio of the sulfate ester salt (D) relative to 100 parts by mass of the aqueous solution containing the antifogging agent is 0.05 parts by mass to 1.0 part by mass.
2. 2. The anti-fogging resin sheet according to claim 1, wherein the cyclodextrin is one member selected from the group consisting of α-cyclodextrin, β-cyclodextrin and γ-cyclodextrin, or a mixture of two or more members selected from the group consisting of α-cyclodextrin, β-cyclodextrin and γ-cyclodextrin.
3. 3. The anti-fogging resin sheet according to claim 1, further comprising a release layer made of silicone oil (E) formed on the other surface of the thermoplastic resin sheet opposite to the surface on which the anti-fogging layer is formed.
4. The anti-fog resin sheet according to any one of claims 1 to 3, wherein the thermoplastic resin sheet is a styrene-based resin sheet.
5. A secondary molded product obtained by molding the anti-fogging resin sheet according to any one of claims 1 to 4.
Citation Information
Patent Citations
Preparation of film or sheet of styrene type resin having improved for registance and releasability
JP1981166234A
Surface treatment agent, coated polymer film and method for producing the same
JP1993287097A
Anti-fogging agent, and anti-fogging resin sheet and molded product
JP2003119451A
Anticlouding resin sheet and secondary molded article using the same
JP2007185951A
Anti-fogging surface-treatment agent and Anti-fogging resin sheet
JP2010037387A